Estudo da estratégia Saúde da Família em Boa Vista, Roraima - Pacobahyba, Luciana Dias (2013)
This study aims to rescue the history of implementation in Boa Vista, as well to analyze the operation of existing units today. The Family Heath Strategy was deployed in the county in 1999 with five units and in 2001 was expanded to 47 units. The research was based on documentary analysis, questionnaires and interviews with team members and managers, as well as observation units surveyed. One of main problems encountered in the implementation process of the strategy was the lack of dialogue with the population and professionals who would work directly on meeting the program objectives. In operation analysis of FHS teams, we perceve a scenario scrapping of units and equipament: incomplet teams, lack of medicines and other materials necessary for the job of the teams. The Family Health Strategy is to Boa Vista the main gateway to the health care of population, that these issues have a direct impact on people's lives.